2000
DOI: 10.1002/1097-458x(200007)38:7<604::aid-mrc682>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Triple proton transfer in crystalline 3,5-dibromo-1H-1,2,4-triazole and 3,5-dichloro-1H-1,2,4-triazole studied by variable-temperature15N NMR andab initio calculations

Abstract: Results are reported of variable‐temperature 15N cross‐polarization magic angle spinning (CP/MAS) NMR experiments performed on [15N2]‐labelled polycrystalline 3,5‐dibromo‐1H‐1,2,4‐triazole (2b) and 3,5‐dichloro‐1H‐1,2,4‐triazole (3b), the synthesis of which is also described. According to the crystal structures these compounds form cyclic trimers in the solid state. The molecular and hydrogen bond structures were compared with those derived from ab initio calculations. The 15N CP/MAS NMR spectra show temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This difference is much larger than expected for a simple protonation-deprotonation in water . In other words, when alkylammonium or ammonium is transferred from a solid halide salt environment to aqueous solution, the nitrogen is shielded strongly, although the protonation state remains the same. For example, a hydration shift of about −12 ppm has been observed for ammonium chloride .…”
Section: Introductionmentioning
confidence: 99%
“…This difference is much larger than expected for a simple protonation-deprotonation in water . In other words, when alkylammonium or ammonium is transferred from a solid halide salt environment to aqueous solution, the nitrogen is shielded strongly, although the protonation state remains the same. For example, a hydration shift of about −12 ppm has been observed for ammonium chloride .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the basis of multiple signals in the 35 Cl NQR spectrum, slightly different from the expected from X-ray data, it has been found that 3,5-dichloro-1,2,4-triazole (1) is present as 1Htautomer with an uncommon phase composition. Later Elguero with co-authors [72] has shown that in crystal, this triazole is present as trimer with intermolecular hydrogen bonds N(1)-H…N(2).…”
Section: Compoundmentioning
confidence: 98%
“…Structure ν, MHz s/n 1 Crystals 2019, 9, x FOR PEER REVIEW 3 of 12 The C(3)-C1(3) and C(5)-C1(5) bond lengths are slightly different [72]. So, it can be anticipated that the spectrum would contain a doublet or two sets of signals.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation